2011
DOI: 10.1007/s10534-011-9426-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper (II) complex of 1,10-phenanthroline and l-tyrosine with DNA oxidative cleavage activity in the gallic acid

Abstract: Copper (II) complex of formulation [Cu-Phen-Tyr](H(2)O)](ClO(4)) (Phen = 1,10-phenanthroline, L: -Tyr = L: -tyrosine), has been prepared, and their induced DNA oxidative cleavage activity studied. The complex binds to DNA by intercalation, as deduced from the absorption and fluorescence spectral data. Scatchard plots constructed from the absorption titration data gave binding constant 2.44 × 10(4) M(-1) of base pairs. Extensive hypochromism, broadening, and red shifts in the absorption spectra were observed. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In order to evaluate the kinetic profile of cleavage of complex 1 (Figure ), a pseudo-Michaelis–Menten analysis was performed and the obtained parameters are shown in Table . This indicates that complex 1 cleaves DNA with a k cat value of 0.89 h –1 and an enhancement over the uncatalyzed DNA cleavage reaction of 2.4 × 10 7 times; these data are consistent with the literature. …”
supporting
confidence: 89%
“…In order to evaluate the kinetic profile of cleavage of complex 1 (Figure ), a pseudo-Michaelis–Menten analysis was performed and the obtained parameters are shown in Table . This indicates that complex 1 cleaves DNA with a k cat value of 0.89 h –1 and an enhancement over the uncatalyzed DNA cleavage reaction of 2.4 × 10 7 times; these data are consistent with the literature. …”
supporting
confidence: 89%
“…One of the earlier studies in EB fluorescence displacement study, the K app value for [Cu(phen) 2 ](ClO 4 ) 2 was found to be 6.67 Â 10 5 M À1 [76]. Yang et al [68], K sv value of ternary copper(II) complex -[Cu-phen-tyr](H 2 O)](ClO 4 ) -was calculated to be 2.88 Â 10 3 M À1 (with gallic acid) and 0.61 Â 10 3 M À1 (without gallic acid). As another example of the fluorescence intercalator displacement assay, the synchronous fluorescence spectroscopy was applied to investigate the competitive interaction of DNA with the bis(1,10-phenanthroline)copper(II) complex cation ([Cu(phen) 2 ] 2+ ) and a fluorescence probe, neutral red dye.…”
Section: Fluorescence Spectroscopymentioning
confidence: 92%
“…Proteins are mainly composed of AAs that act as auxiliary ligands ( 34 ). The AAs found in QA were compared to the FAO/WHO models of reference, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%